Pengaruh Tingkat Kompetensi Pedagogik Guru terhadap Hasil Belajar Siswa pada Mata Pelajaran Fikih di Madrasah Aliyah Al-Mahrusiyah - Atika Nailah Syirva; Zaenal Arifin (Intelektual)
This research aims to determine the influence of teacher pedagogical competence on student learning outcomes in the subject of Fiqh. The method used in this research is a quantitative method. The results of this research show that teacher pedagogical competence influences student learning outcomes in the Fiqh subject, which can be seen from the results of simple linear regression analysis and analysis of the coefficient of determination. From the analysis results, it shows a significance value of 0.001, it can be seen that 0.001 < 0.05. Thus, this research hypothesizes that H1 is accepted and H0 is rejected, with the statement that there is an influence of teacher pedagogical competence on student learning outcomes in the subject of jurisprudence. The results of the analysis of the coefficient of determination show that R Square is 0.336, which means that it indicates that the independent variable in the form of teacher pedagogical competence has an influence on the dependent variable in the form of student learning outcomes by 33.6%, and the remaining 66.4% is influenced by other variables.